ANALISA KEKUATAN MEKANIK KOMPOSIT SERAT SABUT KELAPA (COCOS NUCIFERA) UNTUK PEMBUATAN PANEL PANJAT TEBING SESUAI STANDAR BSAPI - Suhdi, Suhdi S.S.T., M.T; Rosa, firlya (Mesin, 2016)
Composite is a material made from a combination of two or more materials to produce composite materials that have mechanicals properties and the different characteristics of the constituent material. Composit material used is synthetic composite is a composite that uses carbon fiber as a reinforcing material for composite fiberglass. Rock climbing is part of rock climbing equipment are usually made of fiberglass and multiplex where the requirements and standard of rock climbing panel maker have been determined by BSAPI. Manufacture of panels of rock climbing is done by using coconut coir fiber (cocos nucifera) as reinforcement fibers that have been immersion in 5% NaOH for 2 hours. Manufacture of panels of rock climbing using hand lay up, the ratio of resin and catalyst is 1:100, the ratio talk and resin 1:1, the dimensions of the specimen are made using the standard ASTM D638 or tensile testing and ASTM D790 for testing bending BSAPI standard. The results obtained from testing the tensile and bending test is tensile strength 13,034 MPa tensile modulus of elasticity 4359,322 MPa, flexural str gth 24,515 MPa flexural modulus of elasticity 3649,322 MPa. When see from the result from the results of the research panel climbing cococnut fiber is the mechanical strength of the rock climbing fiber panel coconut coil panel has not yet reached the mechanical strength of rock climbing that has been standardized by BSAPI.Key word :Composit , Coconut Fiber , Panel of Rock Clim